(untitled) (Herald of Journalism, 2019)
Over the past five years, eSports traditionally considered to be just the greatest passion for video games, from a class for modest unification gamers in different parts of the world turned into almost a billion industry with a multi-million dollar community. Against this background, it is not surprising that media players and the media are interested in the fast-growing and popular niche. Materials about professional gaming began to appear even in non-profile editions, and broadcasts of eSport competitions were included on cable and satellite TV channels. And therefore, it can be stated that eSports is one of the most actively developing areas of leisure in the world. At the moment, eSports, like traditional sports disciplines (football, hockey, basketball, etc.), is a rapidly expanding business, which invests a large amount of money and involves many people of different professions, including journalists. This article analyzes the phenomenon of eSports broadcasting and its specificity: genre affiliation, characteristic features, features of appearance and commenting. Also, eSports broadcast is regarded as a journalistic product. In addition, there was described as the emergence of eSport and eSports journalism. The scientific significance of this article lies in the fact that the study of eSport journalism is also determined by the fact that, at this moment, this area in the scientific community is practically not represented by any research, either domestic or foreign. Very superficially and uncertainly, scholars just beginning to talk about the phenomenon of “eSports”, but practically nothing can be found about journalistic activities in this area. The practical significance of the work is to show the genre affiliation of eSports broadcasts to journalism, to give an idea of this trend and to determine similarity with other directions. The main purpose of the study is to determine the place of eSports broadcasting in the system of journalistic genres, to demonstrate the media relevance and commercial potential of this type of product.